2020
DOI: 10.1177/1745691620906415
|View full text |Cite
|
Sign up to set email alerts
|

How Do Scientific Views Change? Notes From an Extended Adversarial Collaboration

Abstract: There are few examples of an extended adversarial collaboration, in which investigators committed to different theoretical views collaborate to test opposing predictions. Whereas previous adversarial collaborations have produced single research articles, here, we share our experience in programmatic, extended adversarial collaboration involving three laboratories in different countries with different theoretical views regarding working memory, the limited information retained in mind, serving ongoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 66 publications
2
52
0
2
Order By: Relevance
“…Yet some examples show it is possible to create extended and programmatic collaborative efforts between multiple laboratories, that yield novel insights and contribute to theoretical integration and advancement of robust findings (e.g. Abele‐Brehm, Ellemers, Fiske, Koch, & Yzerbyt, in press; Cowan et al, 2020; Koch, Yzerbyt, Abele, Ellemers, & Fiske, in press; Park et al, 2009; see also Tierney, 2009).…”
Section: Cooperating In a Competitive Systemmentioning
confidence: 99%
“…Yet some examples show it is possible to create extended and programmatic collaborative efforts between multiple laboratories, that yield novel insights and contribute to theoretical integration and advancement of robust findings (e.g. Abele‐Brehm, Ellemers, Fiske, Koch, & Yzerbyt, in press; Cowan et al, 2020; Koch, Yzerbyt, Abele, Ellemers, & Fiske, in press; Park et al, 2009; see also Tierney, 2009).…”
Section: Cooperating In a Competitive Systemmentioning
confidence: 99%
“…This work resulted from an adversarial collaboration—a cooperative research effort undertaken by three groups of investigators who hold different theoretical views regarding working memory (see Cowan et al, 2020 , for an account of this approach, and further details at http://womaac.psy.ed.ac.uk ). One of our two key objectives was to evaluate the impact of stimulus domain and reliance on access to semantic memory representations on the magnitude of age-related dual-task costs in light of three competing theoretical frameworks of working memory that make conflicting claims about how concurrent storage and processing is achieved.…”
Section: The Current Studymentioning
confidence: 99%
“…The first aim is to establish whether age-related dual-task costs can be attenuated or amplified by varying the nature of the processing activity. The second is to evaluate our findings in light of three competing theoretical frameworks of working memory that make conflicting claims about how concurrent storage and processing is achieved (for review see Cowan, 2017 ; Cowan et al, 2020 ; Logie et al, in press-b ). Some theorists claim that working memory is partitioned into several code- or modality-specific resources, which are distinct from domain-general executive resources that facilitate the processing of information (e.g., Baddeley, 2012 ; Baddeley & Logie, 1999 ; Logie, 2011 ; Vandierendonck, 2016 ), or indeed that executive functions arise from the interaction between domain-specific modules ( Eisenreich et al, 2017 ; Hazy et al, 2006 , 2007 ; Logie, 2016 ).…”
mentioning
confidence: 99%
“…In psychology, several teams have developed protocols and checklists that help PACs succeed (Kerr et al, 2018; Latham et al, 1988; Matzke et al, 2015; Mellers et al, 2001; Neir & Campbell, 2013). Cowan et al (in press) have even established an extended adversarial collaboration spanning many studies. Based on their experiences, they also give recommendations for success.…”
Section: Models Of Collaborative Researchmentioning
confidence: 99%
“…This is only one anecdote, but if researchers do not change their beliefs or attitudes given new data, then the impact of large-scale collaborations will be limited. Relatedly, Cowan et al (in press) concluded that they do not believe that adversarial collaboration will lead senior scholars to abandon their theoretical positions, but will nudge them closer toward middle ground.…”
Section: The Future Of Collaborative Research In Gifted Educationmentioning
confidence: 99%